Contralateral dominance to speech in the adult auditory cortex immediately after cochlear implantation - Shader, Maureen; Luke, Robert; McKay, Colette (iScience, 2022)
Sensory deprivation causes structural and functional changes in the human brain. Cochlear implantation delivers immediate reintroduction of auditory sensory information. Previous reports have indicated that over a year is required for the brain to reestablish canonical cortical processing patterns after the reintroduction of auditory stimulation. We utilized functional near-infrared spectroscopy (fNIRS) to investigate brain activity to natural speech stimuli directly after cochlear implantation. We presented 12 cochlear implant recipients, who each had a minimum of 12 months of auditory deprivation, with unilateral auditory- and visual-speech stimuli. Regardless of the side of implantation, canonical responses were elicited primarily on the contralateral side of stimulation as early as 1 h after device activation. These data indicate that auditory pathway connections are sustained during periods of sensory deprivation in adults, and that typical cortical lateralization is observed immediately following the reintroduction of auditory sensory input.
Keywords: Clinical neuroscience; Sensory neuroscience; Bioelectronics